Extremely high reinforcement of high‐density polyethylene by low loading of unzipped multi‐wall carbon nanotubes. Issue 2 (13th August 2021) - Yang, Di; Qi, Xiaohua; Zhang, Wenna; Yang, Na; Chen, Mengyao; Wang, Yao; Huang, Linjun; Wang, Jiuxing; Wang, Shicao; Strizhak, Peter; Tang, Jianguo
Abstract: Multi‐wall carbon nanotubes (MWCNTs) are excellent potential reinforcements for composites due to their high‐mechanical properties. However, a high concentration of MWCNTs is required to reach a good reinforcement. The present study is aimed to show that using unzipped MWCNTs (uMWCNTs) results in an extraordinary enhancement of the mechanical properties of high‐density polyethylene (HDPE). Using 0.2% wt/wt of uMWCNTs as a filler increases the tensile strength and Young's modulus of HDPE by more than 100%. Transmission electron microscopy (TEM), X‐ray diffraction, Raman, Fourier transform infrared spectroscopy, X‐ray photoelectron spectroscopy (XPS), and differential scanning calorimeter (DSC) studies show that the structure and functionality of uMWCNTs and HDPE matrix preserve for their composites. The enhancement in the mechanical properties is mainly associated with an interfacial interaction between separate uMWCNTs sheets and HDPE matrix resulting in increasing the degree of crystallinity and decreasing the crystallite size. Our study provides a new way to fabricate high‐performance composite materials with a low concentration of carbon nanostructures. Abstract :